Research with Agricultural Animals and Wildlife. (16th May 2019) - Cox, Rebecca J; Nol, Pauline; Ellis, Christine K; Palmer, Mitchell V
Abstract: In fiscal year 2016, agricultural animals such as swine, sheep, goats, and cattle represented 10% of the 820 812 animals used in USDA-regulated research. In addition to traditional agricultural animals, research studies using captive wildlife are becoming increasingly important as human and livestock populations encroach upon, and thus expand interactions with, wildlife populations on the landscape. Optimum healthcare of both livestock and captive wildlife in a research setting requires proper husbandry, management, and veterinary care. Regardless of animal species, proper care and management are essential for animal well-being, valid research data, and the health and safety of animal care personnel. Using wildlife in research presents unique challenges as there is generally limited peer-reviewed research on wildlife welfare, husbandry, and nutrition. Animals often become excited during handling or transport, and care must be taken to avoid injury. When severe injuries do occur, differences may exist in methods of euthanasia. Many wildlife species are evolutionarily programmed to conceal signs of illness, making assessment of their condition difficult; moreover, attending veterinarians are often not as experienced in the care of wildlife as they are in the care of traditional laboratory animals or livestock. These differences are further magnified in the context of wildlife field research. The concepts of replace, reduce, and refine are as valid in livestock and wildlife research as in biomedical research, and investigators should work closely with their Institutional Animal Care and Use Committees to ensure humane animal care. The Institutional Animal Care and Use Committee is centrally important in providing guidelines relative to ethical use of animal subjects for research and can serve as a valuable resource for research accountability.